Indian Consumers’ Perspective To Plastic And Plastic Alternatives - Singhal, Piyush (Digital Repository of Theses - SSBM Geneva, 2025)
This research investigates the view of Indian consumers towards plastics and possible alternatives, including the analysis of awareness, attitudes and behaviours to inform workable sustainable material policies and implement sustainable material policies. Other plastic alternatives employed in India are briefly described in the literature review chapter, such as reusable glass and metal containers, compostable and biodegradable bags, products of the areca leaf and bagasse packaging. The assessment of the life of different types of plastics, including paper, glass, aluminium, and bioplastics, is also reflected in this chapter. How consumers view the positives and negatives of using plastic alternatives, the influence of corporate and governmental bodies on consumer behaviour in India and the hindrance to the implementation of plastic alternatives in the country were also evident in this chapter. This section also gives a conceptual framework, a literature gap, and theories. The methodology chapter clearly focuses on the “exploratory design”, a “pragmatic philosophy”, and “inductive reasoning” in order to conduct authentic research based on Indian consumers’ perspective on plastics and sustainable alternatives. This chapter concisely describes that this research is based on both primary qualitative through descriptive statistics and secondary qualitative through thematic analysis, where themes were derived from a systematic literature review. This study investigated the perceptions of Indian consumers to plastics and its substitutes with respect to awareness, attitudes and behavioural adoption. Survey results indicate that although 95 percent of the respondents acknowledge the danger of plastic pollution, the cost, availability, and convenience of alternative materials, including paper, glass, aluminium, and biodegradable plastic, are the factors holding back a mass shift to the latter. Thus, behaviour gap that presents the paradox in that, although many consumers accept that plastic is bad on the environment, they still use it due to cost, and convenience reasons. The main takeaways include enhancing waste management facilities, carrying out specific awareness activities, offering incentive and subsidies to reduce the cost, and making the practice compliant with the cultural norms and the cultural-related innovations.